Pulmonary Manifestations of Primary Sjögren's Syndrome: Underlying Immunological Mechanisms, Clinical Presentation, and Management - Gupta, Sarthak; Ferrada, Marcela A.; Hasni, Sarfaraz A. (Frontiers in Immunology, 2019)
Pulmonary involvement in primary Sjögren’s syndrome (pSS) is an understudied entity with important clinical implications. Its prevalence has been reported in up to 20% of pSS patients. Pulmonary manifestations of pSS are diverse with involvement of airway and/or lung parenchyma. Histopathology of lung lesions suggests a predominance of submucosal mononuclear cell infiltration consisting predominantly of CD4+ T cells. Current understanding of the pathophysiology of lung disease in pSS suggests a similar process driving the pulmonary process as those in the salivary glands, with epithelial cells playing a critical role in the initiation, maintenance, and symptomatology of the disease. Clinical manifestations of lung involvement in pSS are as varied as the underlying pathology and can be vague and non-specific, thus delaying diagnosis. Management options depend on the underlying pathology but are generally limited due to lack of systematic randomized controlled trials. This review helps summarize our current understanding of lung involvement in pSS.